Antenatal Care Experience In Pregnant Women With Gestational Diabetes - Imelda Rismayani Gampur; Herlin Fitriani Kurniawati (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2021)
Background: Globally, one of the increasing health problems that occur during pregnancy is gestational diabetes. The experience of women diagnosed with diabetes in pregnancy has the possibility of experiencing risks such as pre-eclampsia and polyhydramnios (excess amniotic fluid). Babies of mothers who experience this are also at risk for complications such as macrosomia (birth weight > 4000g). Meanwhile, the experience of women during antenatal visits who have a diagnosis of diabetes in pregnancy, often feel anxious about themselves and the fetus and the risks that will occur in the future. Purpose: To review the evidence related to the experience of antenatal care in pregnant women with gestational diabetes. Methods: The method used is the scoping review. created a framework, selecting article studies with Prism Flow Charts, mapping charting data and Critical Appraisal. Results: Based on 9 articles with quantitative and qualitative research types, it was found that there were 8 articles with grade A and 1 article with grade B. The tool used in the scoping review was the Mixed Method Appraisal Tool (MMAT). Based on the articles collected, 4 themes were selected consisting of Antenatal Care (ANC), Knowledge of Pregnant Women, Gestational Impact of Diabetes, and Health Service Efforts. Conclusion: Antenatal care experiences for mothers with gestational diabetes carry a significant risk of maternal and fetal complications and a significant risk of developing type 2 diabetes. Gestational diabetes can contribute to potential emotional imbalances during pregnancy that can trigger depressive symptoms.